1993
DOI: 10.1073/pnas.90.17.8189
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of a ouabain isomer isolated from bovine hypothalamus.

Abstract: Recent reports have shown the presence of a ouabain-like inhibitor of Na+/K+-ATPase in humans. We have purified a bovine hypothalamic Na+/K+-ATPase inhibitory factor (HIF) by using affimity chromatography combined with HPLC. This inhibitor has a molecular weight of 584 as determined by ion-spray mass spectrometry, making it isobaric with ouabain. Glycosidase treatment or acid hydrolysis of HIF released only L-rhamnose, the hexose isomer found in ouabain, as detected by chiral GC/MS. Additionally, enzymatically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
115
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(119 citation statements)
references
References 23 publications
3
115
0
1
Order By: Relevance
“…35 One possible explanation for the discrepant observations from various ouabain assays may be that human endogenous ouabain is a stereoisomer of plant ouabain and is detectable by some antibodies and assay systems 5 -6 but not by others, including our own. However, the NEN ELISA apparently used Ham-lyn's antibody, and in our hands, ouabain was not detected.…”
Section: Discussionmentioning
confidence: 96%
“…35 One possible explanation for the discrepant observations from various ouabain assays may be that human endogenous ouabain is a stereoisomer of plant ouabain and is detectable by some antibodies and assay systems 5 -6 but not by others, including our own. However, the NEN ELISA apparently used Ham-lyn's antibody, and in our hands, ouabain was not detected.…”
Section: Discussionmentioning
confidence: 96%
“…Naphthoylation of HIF (300 ng) followed by RP-HPLC showed that the major derivatization product from HIF eluted slightly earlier than ouabain pentanaphthoate, the major product from ouabain naphthoylation; moreover, CD spectroscopy revealed that this HIF derivative showed no distinct CD, whereas ouabain pentanaphthoate showed a clear positive CD couplet. Although the molecular ion peak of this HIF derivative was not clear, the product was described as HIF pentanaphthoate (13). Subsequent microscale derivatization of OLC (400 ng, gift from Upjohn Laboratories) also gave the same RP-HPLC and CD (''zero-CD'') profiles as those of HIF pentanaphthoate (14).…”
mentioning
confidence: 89%
“…In fact, a material cross-reacting with antibodies against ouabain, digoxin, and digitoxin and inhibiting the sodium pump circulates in increased concentrations in the blood of patients with low renin essential hypertension (1)(2)(3)(4). There has been an intensive search for such substances that has led to the isolation of an ouabain-like inhibitor of the sodium pump from human plasma (5) and an attempt to isolate an isomer of ouabain from bovine hypothalamus (6). Nanogram scale CD structural analysis indicates that both substances show similar properties but are not identical with ouabain (7).…”
mentioning
confidence: 99%